Romanian Prime Minister Gheorghe Tătărescu in the Capitals of the Little Entente: Belgrade (1936) and Prague (1937) - Marusia Cîrstea (Srpska Politička Misao)
The present article presents certain aspects of the relations between Romania, the Czech Republic and Yugoslavia in the interwar period. The fourth decade of the last century in particular was extremely rich in political, diplomatic and military events. Within this international context, Romanian Prime Minister Gheorghe Tătărescu (1934-1937) sought to establish bilateral contacts – with the great powers of Europe, but mainly with the members of the Little Entente – meant to both strengthen bilateral relations and clarify the states’ perspective on the events in progress.